Impact of the productive safety net program on farmers' investments in sustainable land management in the Central Rift Valley of Ethiopia - Adimassu, Zenebe; Kessler, A. (Elsevier, 2015)
This study assesses the impact of the Productive Safety Net Program (PSNP) on farmers' investments in sustainable land management (SLM) practices in the Central Rift Valley (CRV) of Ethiopia. Primary data were collected using a structured and pre-tested questionnaire for a sample of 159 households (82 PSNP participants and 77 non-participants) in four kebeles (the lowest administrative unit in Ethiopia) of two weredas (districts). Using a cross-sectional household survey, propensity score matching (PSM) was used to assess the impact of PSNP on households' investments in soil erosion control and soil fertility management. The PSM results show that the control group of households (non-participants in PSNP) invested more in soil erosion control measures as compared to the treated group of households (participants in PSNP). On the contrary, however, the treated group of households significantly invested more in soil fertility management practices (e.g. inorganic fertilizer and compost) as compared to the control group of households. The negative impact of PSNP on households’ investments in soil erosion control in the treated group of farmers is related to their high labor investment in public works, which is not the case for the non-participants in PSNP. This implies that PSNP should pay more attention to capacity building and awareness raising, which requires a restructuring of the program that would benefit long-term and more sustainable impact on reducing food insecurity and enhancing natural resources in the CRV of Ethiopia.